8.4k views
1 vote
Solve for x 3(7 + 2x) + 3 = 3(5 + x) − 9(x + 1)

User Nsndvd
by
6.3k points

2 Answers

5 votes

Hey there! :)

3(7 + 2x) + 3 = 3(5 + x) - 9(x + 1)

Simplify.

(3 · 7) + (3 · 2x) + 3 = (3 · 5) + (3 · x) + (-9 · x) + (-9 · 1)

Simplify.

21 + 6x + 3 = 15 + 3x - 9x - 9

Add like terms.

6x + (21 + 3) = (3x - 9x) + (15 - 9)

Simplify.

6x + 24 = -6x + 6

Now, we need to isolate x. To do this, we must subtract 24 from both sides.

6x + 24 - 24 = -6x + 6 - 24

Simplify.

6x = -6x - 18

Add 6x to both sides.

6x + 6x = -6x - 18 + 6x

Simlpify.

12x = -18

Divide both sides by 12.

12x ÷ 12 = -18 ÷ 12

Simplify.

x = -18/12

Simplify further.

x = -3/2 OR x = -1 1/2

~hope I helped~


2 votes

Step One

Remove all the brackets

3(7 + 2x) + 3 = 3(5 + x) − 9(x + 1)

21 + 6x + 3 = 15 + 3x - 9x - 9 Collect like terms.

24 + 6x = 6 - 6x Add 6x to both sides.

24 + 6x + 6x = 6 Subtract 24 from both sides

12x = 6 - 24

12x = - 18 Divide by 12

x = - 18 /12

x = - 1.5

Check

3(7 + 2*(-1.5)) + 3 = ? 3(5 + -(1.5) - 9(-1.5 + 1)

3(7 - 3) + 3 =? 3(3.5) - 9*(-1/2)

3*4 + 3 =? 10.5 + 4.5

12 + 3 =? 15 And it checks.


User Simon Suh
by
6.1k points